ChemInform Abstract: New High‐Temperature Pb‐Catalyzed Synthesis of Inorganic Nanotubes. Issue 4 (31st January 2013) - Brontvein, Olga; Stroppa, Daniel G.; Popovitz‐Biro, Ronit; Albu‐Yaron, Ana; Levy, Moshe; Feuerman, Daniel; Houben, Lothar; Tenne, Reshef; Gordon, Jeffrey M.
Abstract MoS2, MoSe2, WS2, and WSe2 nanotubes are prepared by irradiation of 1:1 molar mixtures of MoS2, MoSe2, WS2, or WSe2 and Pb/PbO with highly concentrated solar beam radiation and exposure times of 30—1200 s.